Modelli di crescita limitata dalla bilancia dei pagamenti: storia e panoramica (Balance of payments constrained growth models: history and overview) - Anthony P. Thirlwall (Moneta e Credito, 2012)
Thirlwall’s 1979 balance of payments constrained growth model predicts that a country’s long run growth of GDP can be approximated by the ratio of the growth of real exports to the income elasticity of demand for imports assuming negligible effects from real exchange rate movements. The paper surveys developments of the model since then, allowing for capital flows, interest payments on debt, terms of trade movements, and disaggregation of the model by commodities and trading partners. Various tests of the model are discussed, and an extensive list of papers that have examined the model is presented.